Extensively Reversible Thermal Transformations of a Bistable, Fluorescence‐Switchable Molecular Solid: Entry into Functional Molecular Phase‐Change Materials1. Issue 25 (4th May 2015) - Srujana, P.; Radhakrishnan, T. P.
Abstract Functional phase‐change materials (PCMs) are conspicuously absent among molecular materials in which the various attributes of inorganic solids have been realized. While organic PCMs are primarily limited to thermal storage systems, the amorphous–crystalline transformation of materials like Ge‐Sb‐Te find use in advanced applications such as information storage. Reversible amorphous–crystalline transformations in molecular solids require a subtle balance between robust supramolecular assembly and flexible structural elements. We report novel diaminodicyanoquinodimethanes that achieve this transformation by interlinked helical assemblies coupled with conformationally flexible alkoxyalkyl chains. They exhibit highly reversible thermal transformations between bistable (crystalline/amorphous) forms, along with a prominent switching of the fluorescence emission energy and intensity.